Criteria for Detecting Turn-To-Turn Short Circuit in Stator Windings Using Vector Analysis of Electric Motor Phase Currents - I. V. Zhezhelenko; V. E. Kryvonosov; S. V. Vasilenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2021)
At industrial enterprises, seaports, ships, more than 80 % of all electrical engineering equipment is asynchronous motors. In a number of cases, asynchronous motors operate with a sharply variable load, in an aggressive environment; herewith they receive power from the network with deviations of the power quality indicators from the normative ones, which causes their high damageability. Turn circuits in the stator windings account for about 40 % of cases of damage to the insulation of the asynchronous motors windings. Untimely detection of the initial moment of the appearance of defects in the asynchronous motors or disruption of the operating modes of the supply network and current circuits result in emergency situations of the electrical complex, equipment downtime and damage. The article discusses the issues of diagnostics of non-full-phase modes of current circuits, mains voltages and turn circuits in the stator windings of the asynchronous motors that receiving power from the networks in conditions of voltage asymmetry. The analysis of the vector diagrams of currents, voltages and additional phase angles of the phase currents displacement arising from the asymmetry of the mains voltages and turn circuits in the stator windings has been fulfilled. The results obtained made it possible to formulate criteria for identifying the initial moment of the turn circuit and two-phase modes, both in the network and in current circuits, in stationary modes. A method for non-destructive testing of the asynchronous motors state as well as a device for its implementation has been developed. The method is based on comparing the vectors of the measured phase currents of the asynchronous motors with their calculated values. The article presents the results of modeling the change in the vectors of phase currents from the number of closed turns in the winding of the asynchronous motors. The power series of asynchronous motors was established, for which the sensitivity of detecting the initial moment of the turn-to-turn short circuit is maximum. Analytical results of the dependence of the sensitivity coefficient for turn-to-turn short circuit on the absolute increment of the modules of phase currents and the corresponding phase angles have been obtained.